Composite Anion Exchange Membrane from Quaternized Polymer Spheres with Tunable and Enhanced Hydroxide Conduction Property - Zhang, H.; Shi, B.; Ding, R.; Chen, H.; Wang, J.; Liu, Jian (American Chemical Society, 2016)
© 2016 American Chemical Society. In this research, novel quaternized polymer spheres (QPSs) with a high quaternary ammonium (QA) group loading amount and a controllable structure are synthesized and incorporated into a chitosan (CS) matrix to fabricate a composite membrane. Systematic characterizations and molecular simulation are adopted to elaborate the relationship between the QA structure of QPSs and physical-chemical as well as ion conduction properties of composite membranes. The well-dispersed QPSs generate repulsive interaction to CS chains, endowing the composite membrane with promoted chain mobility and water uptake and thereby enhanced hydroxide conductivity. The QPSs work as hydroxide conductors within the membranes, affording a hydroxide conductivity increase over 80%. As the hopping sites in the membrane, the QA group with moderate OH-combination/dissociation capability exhibits higher OH-conductivity. By comparison, the QA group with the highest or lowest potential displays slightly lower OH-conductivity. Besides, extending the chain length of the QA ligand generates obvious steric hindrance and then impedes OH-combination.